The diagnostic value of auscultation and phonocardiography in pulmonary stenosis and Fallot's tetralogy: their use in differential diagnosis, assessment of severity, prediction of the postoperative result and physiological studies - Vogelpoel, Louis (Division of Cardiology, 2018)
With supplement of 8 reprints .